Projecting the Metropolis: Paris 2024 and the (re)scaling of metropolitan governance. (July 2021) - Geffroy, Damien; Oliver, Robert; Juran, Luke; Skuzinski, Thomas
Abstract: Paris' successful bid for the 2024 Summer Olympics arises in the midst of a grand rethinking of the politics of regional and local development in the Île-de-France region. Paris 2024 also emerges at a time when the International Olympic Committee (IOC) is struggling to find cities willing to host the Olympics and has introduced a series of reforms to help recruit and motivate potential bid cities to consider how an Olympic project might be integrated into existing patterns of urban development. This exploratory research examines the blending of the Grand Paris regional development project and the 2024 Olympic ambition. Incorporating results from semi-structured interviews with seven key informants who possess specialized knowledge and are involved with governance mechanisms of the Île-de-France region and urban megaevent development, we explore how the Paris 2024 Olympic Games are being leveraged to facilitate metropolitan transformation. In the highly fragmented institutional setting of the Île-de-France region, negotiating site locations for Olympic facilities and establishing legacy or heritage objectives for the Olympic Games has important implications for the development of an institutional framework for metropolitan governance. Highlights: Project-based governance transformation The use of mega-events to foster a vision of metropolitan consensus in a capitalist democratic context The leveraging of the Olympic bidding and hosting process to produce institutional change International Olympic Committee's Agenda 2020 and the potential to inform territorial dynamics